ANALISIS KELAYAKAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI BAWANG MERAH DI DESA JATIADI KECAMATAN GENDING KABUPATEN PROBOLINGGO - Sholehuddin Sholehuddin; Dwi Susilowati; Sri Hindarti (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This study aims to analyze the feasibility of onion farming and find out the factors that influence the production of shallot farming, the determination of the location of the research was done intentionally (purposive) in Jatiadi Village, Gending District, Probolinggo Regency with a total sample of 35 shallots farmers. Sampling is done by the method of sample random sampling. The data analysis method used is the R / C Ratio analysis. The results showed that onion farming is feasible to be developed with a total R / C Ratio of 1.8. Factors that influence the production of onion farming using the Cobb-Douglass function analysis. From the results of the analysis of factors that significantly affect the onion, namely land area, labor, pesticides, while the factors that do not affect the production of shallots are seeds and fertilizer.